Characteristics of Roof Movement and Ground Pressure Behavior of Gob-side Entry Retaining by Roof Cutting in Continuous Mining. Issue 5 (October 2020) - Li, Minzu; Ma, Zimin; Wang, Haohao; Zhang, Yong; Jia, Fayuan
Abstract: Gob-side entry retaining by roof cutting (GERRC) technology has been widely used in China, but application research of the entry-retaining technology in continuous mining is relatively scarce. Based on the analysis of the technology of continuous mining and GERRC, this study adopted the methods of theoretical analysis and in-field monitoring of ground pressure and behavior to obtain the roof movement characteristics and ground pressure distribution law during the entire process of roof directional pre-splitting, entry retaining, and entry reusing. Using the engineering geological conditions and analysis of field data of Dianping coal mine in Shanxi Province, the principal design parameters and technological process of GERRC in continuous mining were obtained. The structure model of the retained roadway roof in continuous mining was constructed to study roof movement patterns and the mechanism of stability control of the retained roadway. The movement regularity of the overlying strata in the mining and entry-retaining stage was obtained, enriching the theory of roof structure evolution and stress transfer under the condition of continuous mining with GERRC. The research results provide significant support for further popularization and application of the technology of GERRC.